Proceedings of the International Conference on English Language Teaching (ICONELT 2017) 2018
DOI: 10.2991/iconelt-17.2018.2
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perspectives towards Self-Directed Learning out of Classroom

Abstract: -One of the critical issues inIndonesia is the tendency of the students to depend very much on their teachers and act passively in the classroom. Meanwhile, in this digital era, students who only depend on the teacher in the class would likely to be left behind and make slower progress on their learning achievement. Due to the limited amount of time in class, the learners are encouraged to be responsible for their own learning and learning independently beyond the classroom called as selfdirected learning. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The teacher did not give students tasks; therefore, there was no feedback at the end of the activity. This activity does not reflect the practice of self-directed learning (Humaira & Hurriyah, 2018;Sert & Boynueğri, 2017). The last phase of the learning process must engage the students in reflection of learning, engage their prior knowledge, and draw the connection of what they learn inside and outside of the school (Hill et al, 2020;Zhu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The teacher did not give students tasks; therefore, there was no feedback at the end of the activity. This activity does not reflect the practice of self-directed learning (Humaira & Hurriyah, 2018;Sert & Boynueğri, 2017). The last phase of the learning process must engage the students in reflection of learning, engage their prior knowledge, and draw the connection of what they learn inside and outside of the school (Hill et al, 2020;Zhu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…They learn by their responsibility with guidance from the teacher or instructor. Self-directed learning is also known as self-planned learning or independent learning, which is a process where learners take their own responsibility (Hanik, 2020;Humaira & Hurriyah, 2018). Self-Directed learning also affects the critical thinking of the students, and it influences the other aspects of education (Sert & Boynueğri, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Those feedbacks were useful to improve the students' motivation in doing the next assignments. According to Humaira and Hurriyah (2018), giving feedback is important for students' self-reflection about the assignment that has been done by the students, and in this observation, the teacher only giving some magic words that make it the students difficult to make self-reflection to their work.…”
Section: Asking Questionmentioning
confidence: 99%
“…There are several skills that should be mastered by the students usually called 4C which are collaboration, communication, creativity, and critical thinking (Yu & Wan Mohammad, 2019). The study was conducted by Humaira and Hurriyah (2018) has showed by applying real self-directed learning in the learning process, the students have high motivation and confidence in the learning because most of the students could be considered as having moderate self-direction. The next study was conducted by Salleh et al (2019) has showed that self-directed learning has a good impact on the learning process, especially for life-long learning.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to add insight into SDL. Studies conducted to explore students' perspectives on SDL outside the classroom found that most students can be considered to have moderate self-direction Humaira and Hurriyah (2018). However, they experienced some difficulties in determining appropriate learning strategies, evaluating learning, and doing self-reflection.…”
Section: Introductionmentioning
confidence: 99%